Penerapan Problem Based Learning Dalam Pembelajaran Matemtika Untuk Peningkatan Kemampuan Pemecahan Masalah Pada Siswa Kelas VIII Semester II SMPN 1 Teras Tahun 2014/2015 - Hidayah, Marfuqotul; , Prof. Dr. Sutama, M.Pd (2015)
The purposeof research to describe the increase in problem solving ability math through learning strategies Problem Based Learning (PBL) with students of SMP Negeri 1 Teras C class VIII 2014/2015 year.The type of research is kualitatif approach with classroom action research desain. The research to perform in SMP Negeri 1 Teras. The technique of collecting data through observation, testing, field notes, and documentation. The data obtained in the form of scores in the cycle I and cycleII. Data analysis techniques performed by the method of flow. In crease student in mathematical problem-solving ability: 1) the studentis able to understand the problem before action 43,75%; the firs cycle 84,375%; and second cycle 93,75%, 2) students are able to plan the settlement of the problem before action 34,375%; the first cycle 78,125%; and the second cycle 84,375%. 3) the studentis able to carry out the appropriate problem resolution before the action plan 28,125%; the first cycle 87,5%; and second cycle 90,625%. 4) students were able to see back for all the steps before the actions 21,875%; the first cycle 78,125%; and second cycle 84,375%. Based on the description above concluded that the application of learning strategies problem based learning can improve math problem solving ability.